Diagnosis Molekuler Infeksi Ganda Avian Influenza Virus dan Newcastle Disease Virus pada Ayam Petelur Komersial - Maya Ekaningtias; Hastari Wuryastuty; Raden Wasito (Yayasan Tajuk Indonesia, 2025)
Viral infections in commercial poultry are not always caused by a single pathogen and may involve concurrent infections by multiple viruses. Avian influenza virus (AIV) and Newcastle disease virus (NDV) are among the most important pathogens affecting poultry health, as they often induce overlapping clinical manifestations and tissue alterations, leading to high mortality rates and substantial economic losses. This study investigated the presence of these viruses in commercial layer chickens exhibiting neurological signs, including torticollis and leg paralysis, accompanied by hemorrhagic lesions in the digestive tract, using a molecular diagnostic approach. Serum and digestive tract samples were collected from affected layer chickens originating from commercial farms with reported disease outbreaks. All samples were analyzed using simplex reverse transcriptase polymerase chain reaction (sRT-PCR). RNA extraction for AIV was performed using a commercial kit, while NDV RNA was isolated using Trizol reagent. Viral detection was carried out using specific primers targeting the nucleoprotein gene of AIV and the conserved region of NDV, producing amplicons of 552 bp and 320 bp, respectively. Amplified products were visualized by electrophoresis on 1.5% agarose gel. The results demonstrated the presence of AIV-specific amplicons in serum samples and NDV-specific amplicons in digestive tract tissues, indicating concurrent infection by both viruses in the examined layer chickens. These findings confirm that sRT-PCR is a reliable molecular tool for the confirmation and differentiation of AIV and NDV infections in poultry cases presenting similar clinical signs and pathological lesions.